Glucose Transporter-1 (GLUT1) Deficiency Syndrome: Diagnosis and Treatment in Late Childhood - Gramer, Gwendolyn; Wolf, Nicole I.; Vater, Daniel; Bast, Thomas; Santer, René; Kamsteeg, Erik-Jan; Wevers, Ron A.; Ebinger, Friedrich (Neuropediatrics, 2012)
Background Typical cases of glucose transporter-1 deficiency syndrome (GLUT1-DS) present with early-onset epilepsy. We report symptoms, diagnostic results, and effects of therapy in two patients diagnosed with GLUT1-DS at the age of 10 and 15 years, respectively.Patients Patient 1: After four cerebral seizures in the first 2 years of life the patient was seizure-free but showed a complex movement disorder, expressive speech disorder, and mental retardation. Ratio of cerebrospinal fluid (CSF) to blood glucose was 0.41 (reference range 0.65 ± 0.1), molecular genetic testing confirmed GLUT1 deficiency with the novel pathogenic mutation c.1377dupC (p.Phe460LeufsX3) in the SLC2A1 gene. Following 9 months of ketogenic diet started at the age of 10 years, there was distinct improvement of speech and movement disorder. Patient 2 showed pharmacorefractive epilepsy, mental retardation, and a mild movement disorder. At the age of 15 years, extensive intake of food with high fat content was observed. Ratio of CSF to blood glucose was 0.41 (reference range 0.65 ± 0.1). The pathogenic mutation c.634C>T (p.Arg212Cys) was found in the SLC2A1 gene.Conclusion Self-induced high-fat diet can be a hint toward GLUT1-DS. Ketogenic diet can be beneficial even when started in late childhood, although it may take several months to achieve a positive effect.
Keywords: GLUT1 deficiency syndrome; ketogenic diet; movement disorder; seizures; SLC2A1 gene